The Representation of Egyptian History in Maher Batuti’s Novel Al Futuuhat Al Barisiyyah: A New Historicism Study - Sulis Jumardan; Moh Zawawi (Raja Zulkarnain Education Foundation, 2025)
A novel is not merely a work of fiction, it can also serve as an archive of history, both in documenting global events and recording personal responses to occurrences that are rarely preserved in official records. This study departs from a series of excerpts from Maher Batuti’s Al Futuuhat Al Barisiyyah which portrays Egyptian history after 1952, including humanitarian tragedies, political conflicts, and social dynamics in the Middle East. Several key issues highlighted in the novel include civilian massacres caused by Israeli air raids, Egypt’s defeat in the Six-Day War or the Naksa of 1967, the dilemmas of the Egyptian diaspora in France, as well as Gamal Abdel Nasser’s political repression against the leftists and the Muslim Brotherhood. The objectives of this study are to reveal how fiction can function as an alternative historical archive, to analyze the representation of Egyptian political history within a literary text, and to uncover the causes and impacts of Egypt’s political decline as depicted in the novel. This research employs a qualitative descriptive method through literary text analysis combined with historical inquiry. Data were collected through intensive reading of the novel, examination of historical articles, and archival studies. The findings indicate that the novel presents Egyptian history from a more humanistic perspective, capturing experiences of diaspora, political wounds, and the transition of leadership from Nasser to Sadat. Egypt, once depicted as a tolerant and beautiful nation, is shown to have hardened under Nasser’s policies, culminating in the Naksa tragedy and conflicts with the Muslim Brotherhood. Thus the novel constructs an alternative history that not only addresses political events but also records marginal voices often overlooked and omitted in official historiography.